Caribbean Report 29-04-1997 - Gordon, Warren (anchor); Orr, Carol (correspondent); Morris, Bill (interviewee); Major, John (interviewee); Blair, Tony (interviewee); Ashdown, Paddy (interviewee) (The British Broadcasting Corporation, 1997)
With a day and a few hours of campaigning left before one of Britain’s most crucial general elections leaders of the two main parties have embarked on marathon efforts to try to win over wavering voters. Also, the issues at stake for black businesses in Britain ahead of the general elections are looked into and the Labour Party’s relationship with the unions is discussed. Next, Cuba is to hold nationwide military manoeuvres. Cuban officials say that exercises involving the air force and anti-aircraft defence forces will take place in every province. Next, the exiled former President of Haiti, Jean-Claude Duvalier has broadcast a message to Haitians for the first time since he left in 1986. Finally, in Britain the question of voter apathy among youths, both white and Afro-Caribbean is looked at.
1. Headlines (00:00-00:24)
2.With less than thirty six hours to the start of voting in Britain's general elections a mixed outlook for black businesses in whoever wins. Prime Minister John Major, Tony Blair, Labour Leader and Paddy Ashdown of the Liberal Democrat Party are interviewed. Carol Orr reports (00:32-09:23)
3. Military manoeuvres in Cuba today (09:24-09:39)
4. Former President of Haiti Jean-Claude Duvalier addresses the nation for the first time since he left in 1986. Michael Norton reports (09:40-10:27)
Keywords: Elections -- Britain.; Black businesses -- Britain.; Military manoeuvres -- Cuba.; Duvalier, Jean-Claude.; Voter apathy.